Immunosuppressive Therapy-Related Cardiovascular Risk Factors in Renal Transplantation: A Narrative Review - Chiara Paccagnella; Stefano Andreola; Alessia Gambaro; Giovanni Gambaro; Chiara Caletti (Cardiorenal Medicine)
Background: Kidney transplantation is the best treatment for patients with chronic renal failure, capable of improving life expectancy and the risk of death from all causes, which, however, remains higher than in the general population. The leading cause of death in transplant patients is cardiovascular events, burdened by a significant impact brought about by anti-rejection therapy. Experimental and clinical studies to date show that in kidney transplant recipients, traditional cardiovascular risk factors (hypertension, diabetes, dyslipidemia, obesity, tobacco, etc.) may be exacerbated or worsened by the dysmetabolic effects of immunosuppressive drugs, which may also result in additional risk factors such as proteinuria, anemia, and arterial stiffness. The aim of this review was to provide an in-depth evaluation of the effect of immunosuppressive treatments on cardiovascular risk factors. Summary: We have investigated and described the main cardiovascular risk factors related to immunosuppressive drugs. We searched for relevant scientific articles in medicine, transplant, cardiologic, and nephrological journals in major medical science libraries. Key Messages: Immunosuppressive drugs allow graft survival and successful bunking of the transplant; however, they are not without significant side effects and should always be prescribed weighing the risk/benefit ratio and the individual patient’s therapeutic needs.